Nonlinear forced vibrations of curved microbeam resting on nonlinear foundation using the modified strain gradient theory - Allahkarami, F.; Allahkarami, F.; Nikkhah-bahrami, M. (Прикладная механика, 2018)
The nonlinear forced vibrations of a curved micro- beam resting on the nonlinear foundation are examined. The equations of motion are derived using the Hamilton's principle and the modified strain gradient theory which is capable to examine the size effects in the microstructures. The nonlinear partial differential equations of motion are reduced to a time-dependent ordinary differential equation containing quadratic and cubic nonlinear terms. A frequency response of the curved microbeam for the primary resonance is determined using multiple time scales perturbation method. From the application point of view, the frequency response curves may be useful to select the optimum values of design parameters. The effects of geometry parameters and foundation moduli on the vibration behavior of the curved microbeam are illustrated. Розглянуто нелінійні змушені коливання викривленої мікробалки, яка лежить на нелінійній основі.Рівняння руху отримані на основі принципу Гамільтона і модифікованої теорії градієнтів деформації. що дає змогу вивчити ефекти розміру в мікроструктурі. Нелінійні рівняння руху з частинними похідними зведено до залежного від часу рівняння, яке містить квадратично і кубічно нелінійні члени. Визначено частотну характеристику викривленої балки для першого резонансу, для чого використано метод багатомасштабних у часі збурень. З прикладної точки зору, криві частотної характеристики можуть бути корисними для вибору оптимальних значень параметрів при проектуванні. Проілюстровано вплив геометричних параметрів модулів основи на коливання викривленої мікробалки.